Rate Setting for Labour Costs Related to Pharmacovigilance System Inspections - M. Abdrakhmanov; R. N. Alyautdin; A. E. Krasheninnikov; B. K. Romanov (Безопасность и риск фармакотерапии, 2022)
The inspection of pharmacovigilance systems is regulated by the Good Pharmacovigilance Practices (GVP) and local laws and regulations. Inspections may be carried out by audit teams of competent authorities as part of regulatory activities or business agreements. So far, there have been no studies dealing with rate setting for competent authorities labour costs in connection with onsite or documentary inspections of pharmacovigilance systems.The aim of the study was to develop scientifically valid rate setting criteria for labour costs related to onsite or documentary inspections of pharmacovigilance systems.Materials and methods: the assessment of labour costs was carried out by surveying experts of two Eurasian Economic Union (EAEU) countries who have experience in preparing and conducting evaluation and inspection of pharmacovigilance systems. The calculation of the experts’ time costs was performed automatically using the CrocoTime software. The expected workload for experts in 2022 was estimated based on the reports over the last 5 years (2016–2020) containing information on the number of foreign marketing authorisations, and the number of medicines under development according to national registers of medicinal products of the EAEU member states.Results: the study calculated the average expert labour costs and estimated workload for the EAEU competent authorities in 2022. It was demonstrated that the average labour costs are comparable in EAEU member states, however, estimated amount of labour may change (both increase or decrease).Conclusions: further study of rate setting for labour costs related to pharmacovigilance documentary inspections and study of competent authorities staffing could be performed by a dedicated division, e.g. of the Eurasian Academy of Good Practices. A constructive discussion of approaches to the improvement of control over pharmacovigilance systems will increase availability of efficacious and safe medicines of assured quality for the population and help pharmaceutical companies and regulatory authorities manage financial and reputational risks.